2016
DOI: 10.1016/j.ajpath.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1B1 Contributes to the Development of Angiotensin II–Induced Aortic Aneurysm in Male Apoe−/− Mice

Abstract: Cytochrome P450 (CYP) 1B1 is implicated in vascular smooth muscle cell migration, proliferation, and hypertension. We assessed the contribution of CYP1B1 to angiotensin (Ang) IIeinduced abdominal aortic aneurysm (AAA). Male Apoe À/À /Cyp1b1 þ/þ and Apoe À/À /Cyp1b1 À/À mice were infused with Ang II or its vehicle for 4 weeks; another group of Apoe À/À /Cyp1b1 þ/þ mice was coadministered the CYP1B1 inhibitor 2,3 0 ,4,5 0 -tetramethoxystilbene (TMS) every third day for 4 weeks. On day 28 of Ang II infusion, AAAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
5
15
0
Order By: Relevance
“…Strikingly, the most prominent difference in elastin remodeling between Cyp1b1 +/+ and Cyp1b1 −/− mice was observed in grades 3 and 4 of the elastin degradation index, implying that a breakage of elastin fibers in Cyp1b1 +/+ mice might have permitted medial SMCs to breach the ECM and migrate to form neointima. These results, coupled with our in vitro findings of attenuated migration of VSMCs by Cyp1b1 gene disruption, along with our previous work in mouse models of atherosclerosis and abdominal aortic aneurysms,28, 29 indicate that CYP1B1 plays an important role in elastin metabolism/degradation . …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Strikingly, the most prominent difference in elastin remodeling between Cyp1b1 +/+ and Cyp1b1 −/− mice was observed in grades 3 and 4 of the elastin degradation index, implying that a breakage of elastin fibers in Cyp1b1 +/+ mice might have permitted medial SMCs to breach the ECM and migrate to form neointima. These results, coupled with our in vitro findings of attenuated migration of VSMCs by Cyp1b1 gene disruption, along with our previous work in mouse models of atherosclerosis and abdominal aortic aneurysms,28, 29 indicate that CYP1B1 plays an important role in elastin metabolism/degradation . …”
Section: Discussionsupporting
confidence: 85%
“…Our finding that the CYP1B1 inhibitor 2,3′,4,5′‐tetramethoxystilbene minimizes hypertension, atherosclerosis, and abdominal aneurysms,5, 28, 29 while also attenuating neointimal growth in wire‐injured carotid artery of Cyp1b1 +/+ male mice, further supports our hypothesis that CYP1B1 is required for neointimal growth and suggests an important translational implication of this work. Thus, CYP1B1 could serve as a potential target for the development of novel agents for the treatment of restenosis after balloon angioplasty, or to coat drug‐eluting stents as antiproliferative agents in male mice.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, the protective effects of CYP1B1 in female rodents have been attributed to CYP1B1-mediated metabolism of estrogen to 2-methoxyestradiol [ 96 , 97 ]. Furthermore, CYP1B1 has been shown to contribute to the development of atherosclerosis, hypertension, and angiotensin II-induced aortic aneurysm in male apolipoprotein E-deficient mice [ 98 , 99 ]. In vitro studies have suggested the contribution of CYP1B1-mediated formation of genotoxic metabolites and DNA adducts in the development of atherosclerosis by polyaromatic hydrocarbons [ 100 , 101 ].…”
Section: Cyp1b1mentioning
confidence: 99%